2018
DOI: 10.17576/jsm-2018-4711-12
|View full text |Cite
|
Sign up to set email alerts
|

(-)-Glaciantarcin, a New Dipeptide and Some Secondary Metabolites from the Psychrophilic Yeast Glaciozyma antarctica PI12

Abstract: A new dipeptide, (-)-glaciantarcin (1) and three known compounds, cyclo(-Pro-Gly) (2), 1-(2-deoxypentofuranosyl)-5methyl-2,4(1H,3H)-pyrimidinedione (3) and vidarabine (Ara-A) (4), were isolated from Glaciozyma antarctica PI12, a cold-adapted yeast. The chemical structures were elucidated by FT-IR, NMR and mass spectrometry. The cytotoxicity and antioxidant activities of compounds 1-4 were evaluated by using the MTT bioassay on MCF-7 (human breast cancer cell line), PC-3 (human prostate cancer cell line) and HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, marine organisms have emerged as a noteworthy natural source of cGP . This review primarily focuses on marine sources of cGP up to 2022, due to the prevalence of cGP in marine natural product chemistry ( Table 1 ) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Interestingly, the majority of collection sites for marine sources of cGP are located in tropical and subtropical coastal areas [ 47 ], and several sites are closely associated with mangroves.…”
Section: Sources: Marine Origins Endogenous Biological Transformation...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, marine organisms have emerged as a noteworthy natural source of cGP . This review primarily focuses on marine sources of cGP up to 2022, due to the prevalence of cGP in marine natural product chemistry ( Table 1 ) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Interestingly, the majority of collection sites for marine sources of cGP are located in tropical and subtropical coastal areas [ 47 ], and several sites are closely associated with mangroves.…”
Section: Sources: Marine Origins Endogenous Biological Transformation...mentioning
confidence: 99%
“…Augmenting the topological polar surface area and introducing three-dimensional spatial Based on a structure-activity relationship study of Spodoptera exigua serotonin-specific receptor (Se-5HTR) inhibitors, Hasan et al linked the cGP fragment to the end of the carbon chain, which enhanced the specificity and competitive inhibitory activity of compound 34 against Se-5HTR (Figure 8c) [92]. This modification resulted in a two-order-of-magnitude improvement in the in vitro immunosuppressive activity compared to the prototype compounds (32)(33). Thus, leveraging the outstanding drug-likeness and bonding affinity advantages of cGP provides efficient pharmaceutical building blocks for lead optimisation in the early stages of drug discovery.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…The sample was eluted using n-hexane/ethyl acetate (EtOAc) (in ascending polarity manner) and finally with MeOH to afford 10 fractions. Purification of fraction 6 was carried out using a radial chromatography (RC) with silica gel plate of 1 mm thickness eluted with 95:5 n-hexane-EtOAc in 5% polarity increment to yield compounds 1 (25 mg) (Rosandy et al 2013;2018).…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…The procedures of cultivation of yeast G. antarctica PI12 and isolation of compound were described in Rosandy et al (2017Rosandy et al ( , 2018.…”
Section: Biological Materials Cultivation Of Yeast and Isolation Of mentioning
confidence: 99%
“…Early studies regarding the chemical constituents of cold-adapted yeast Glaciozyma antarctica PI12 (Di Menna 1960;Fell et al, 1969;Donachie 1995;Turkiewicz et al, 2005;Connell et al, 2008;Turchetti et al, 2011) revealed the presence of a new diketopiperazine i.e. (-)-Glaciantarcin, together with five known diketopiperazine and two pyrimidine (Rosandy et al, 2017(Rosandy et al, & 2018Alwi et al, 2017s). This paper reported for the first time the isolation and detailed characterization of a PCA from yeast G. antarctica PI12…”
Section: Introductionmentioning
confidence: 99%